Interaction of drugs of abuse and microRNA with HIV: a brief review - Pilakka-Kanthikeel, Sudheesh; Nair, Madhavan P. N. (Frontiers in Microbiology, 2015)
MicroRNAs (miRNAs), the post-transcriptional regulators of gene expression, play key roles in modulating many cellular processes. The changes in the expression profiles of several specific miRNAs affect the interactions between miRNA and their targets in various illnesses, including addiction, HIV, cancer etc. The presence of anti-HIV-1 microRNAs (which regulate the level of infectivity of HIV-1) have been validated in the cells which are the primary targets of HIV infection. Drugs of abuse impair the intracellular innate anti-HIV mechanism(s) in monocytes, contributing to cell susceptibility to HIV infection. Emerging evidence has implicated miRNAs are differentially expressed in response to chronic morphine treatment. Activation of mu opioid receptors (MOR) by morphine is shown to down regulate the expression of anti-HIV miRNAs. In this review, we summarize the results which demonstrate that several drugs of abuse related miRNAs have roles in the mechanisms that define addiction, and how they interact with HIV.